Chef’s Table Experience as a Soft-Power and Nation-Brand Mechanism in MICE Marketing: A PLS-SEM Test of an Integrated Five-Layer Model in Thailand - Wongjunpen, Punnaporn; Siriwong, Phitak; Wilainuch, Pairote (Arts of Management Journal, 2026)
Although the experience-economy, soft-power, and nation-branding literatures each address gastronomic destination experiences, they have remained largely parallel, leaving unspecified how an on-site dining experience translates into perceived national competitive advantage. This study examined (1) the influence of four exogenous 4E experience dimensions (entertainment, education, escapism, aesthetics) on five cultural-value mediators (authenticity, storytelling, localness, participation, memorability) within the Chef’s Table experience; (2) how these mediators transmit effects to soft-power perception, nation-brand perception, national image, and trust-and-affect among MICE delegates in Thailand; and (3) the variance in perceived national competitive advantage explained by the integrated five-layer model and its out-of-sample predictive performance. A purposive sample of 200 MICE delegates attending Chef’s Table programs in Bangkok, Chiang Mai, Pattaya, and Phuket during the 2024–2025 cycle, screened for firsthand attendance, completed a 57-item reflective questionnaire measuring 14 latent constructs on a 5-point Likert scale. Data were analyzed using PLS-SEM in SmartPLS 4. All eight paths from 4E antecedents to cultural-value mediators were supported, with education and escapism dominant, channeled through localness and participatory co-creation, respectively. All eleven paths from cultural value through soft-power and nation-brand perception into national image and trust-and-affect were supported, with participation the strongest antecedent of nation-brand perception and trust-and-affect the most strongly predicted construct. The integrated five-layer model explained 56.7% of the variance in perceived national competitive advantage and demonstrated robust out-of-sample predictive performance. The findings supply soft-power theory with its long-missing microfoundation, provide Thai DMOs with a sequenced lever map for evidence-based gastrodiplomatic investment, and integrate three previously parallel literatures into a single, predictively valid mechanism linking individual gastronomic experience to national competitive advantage.